2020
DOI: 10.5539/gjhs.v12n3p103
|View full text |Cite
|
Sign up to set email alerts
|

Facts, Traditions, and Complications of Skin Whitening Products among Female Students in Sudan: A Cross-Sectional Study

Abstract: The increased use of skin whitening products serves as a significant challenge for the health care unit. The progressive use of the whitening products exposes individuals to various risk factors and skin-related complications. This study aims to determine the usage of skin-whitening products among female students at Ibn Sina University, Sudan. It further intends to assess the complications and risk factors that may emerge due to the increased use of skin whitening products. It used a descriptive cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
2
1
Order By: Relevance
“…Only (18.6%) experienced complications in this study. Which is much lower than what was found in Ibn-Sena University, where (86%) experienced complications (5) . This difference might be because the majority in this study practiced skinwhitening for a short duration.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Only (18.6%) experienced complications in this study. Which is much lower than what was found in Ibn-Sena University, where (86%) experienced complications (5) . This difference might be because the majority in this study practiced skinwhitening for a short duration.…”
Section: Discussioncontrasting
confidence: 58%
“…(4) . The users of skin whitening products usually are of the younger population for example 72 percent of the women who practice skin whitening in Lahore, India fall between (20-30) years (5) The history of skin bleaching is often traced to the Elizabethan age of powder and paint, nowadays skin bleaching is practiced disproportionately within communities "of color." Especially among people of African descent.…”
Section: Introductionmentioning
confidence: 99%
“…The results the study conducted in Sudan, revealed that age is one of the prime contributors which promotes the usage of skin whitening products. 10 Most respondents who use SLPs were not married in this study. A similar study conducted in Nigeria showed that most of SLP users were single (69.8%).…”
Section: Discussionmentioning
confidence: 77%